Ecological Knowledge Management and Creative Economy Upgrading of Krajood Products in Phru Khuan Khreng, Thailand - Boonchat Mekkaeo; Anucha Thaisanong; Nattanicha Homgate; Nannapat Prompetch; Khemmathat Suwanmanee (Journal of Education Psychology and Social Development, 2026)
This in-depth qualitative case study investigates the dynamics of ecological knowledge management and the creative upgrading of Krajood handicrafts in the Phru Khuan Khreng wetland, Nakhon Si Thammarat. The research aims to explore how indigenous wisdom adapts to contemporary economic pressures while maintaining its ecological integrity. Data were collected through in-depth interviews with five local sages, participant observations of two community enterprises, and focus group discussions with three interdisciplinary experts. The findings reveal three pivotal dynamics: (1) Upstream Ecological Wisdom, specifically the "mud-soaking" technique which utilizes specific geological attributes as a natural fiber conditioner; (2) Midstream Technological Transition, where motorized machinery is integrated with "tacit knowledge" to enhance production efficiency without compromising traditional quality; and (3) Downstream Creative Management, utilizing identity-based storytelling and cross-material design to enter premium markets. From an educational psychology perspective, these dynamics represent a robust Community of Practice and a form of Situated Learning, where intergenerational knowledge is transmitted through social participation and ecological interaction. The study concludes that the structural adaptation of this wisdom system is essential for sustainable social development, fostering community resilience and the preservation of cultural capital within the global creative economy. The results offer a framework for integrating indigenous knowledge into place-based education and community-driven innovation.